(untitled) (American Journal of Technology and Applied Sciences, 2024)
In this article, it is analyzed that among the people of Sufism (mystics), poets, thinkers-sages emerged who left many artistic, philosophical, theological works in Arabic, Persian, Turkish and other languages.